Impact of brand authenticity on word-of-mouth for tourism souvenirs - Shoji Tanaka; Changju Kim; Hiroyuki Takahashi; Akihiro Nishihara (Cogent Business & Management, 2024)
Although prior studies have shown that consumers who perceive brand authenticity are more likely to spread word-of-mouth (WOM) recommendations, the underlying explanatory mechanism in the context of souvenir products in tourism remains unclear. To fill this gap, this study presents a hypothetical framework that elucidates the mechanisms through which brand authenticity influences positive WOM and identifies the boundary condition that enhances its effects, drawing on consumer inference theory. Through a survey conducted on a fictitious food souvenir brand in Uji City, Kyoto Prefecture, a prominent tourist destination in Japan, we confirm that a company's commitment to the brand's roots, as inferred from brand authenticity, mediates the relationship between brand authenticity and positive WOM. Additionally, we show that this indirect effect is strengthened by consumers' perceptions of the craftsman's passion. These findings offer novel insights into marketing communication strategies aimed at amplifying positive WOM for future food souvenirs in a tourism context.
Keywords: 650; brand authenticity; company's commitment to the brand's roots; craftsman passion; food souvenir; tourism; word-of-mouth